The Relationship Between Participation in Extracurricular Activities and Academic Achievement of FIK Uncen Students Class of 2017 - Muhammad Teguh Prasetyo; Yohanis Manfred Mandosir; Kurdi Kurdi (IKIP Budi Utomo Malang, 2021)
The purpose of this study was to determine the correlation of participation in extracurricular activities with the academic achievement of FIK Uncen students class 2017. The reason behind the researcher lifting the title of this research is because students' interest in extracurricular is so low. In essence, where extracurricular activities have a relationship with academic achievement. This research includes correlational research. The sample in this study were FIK Uncen 2017 students, totaling 26 people. There are two data collection instruments used, namely questionnaires used to measure participation in extracurricular activities and documentation (Study Results) to see the academic achievements of FIK Uncen 2017 students. The data collection techniques used were in three stages, namely interviews, distributing questionnaires, and achievement data. academic. There are two stages of data analysis technique, namely expert judgment validity testing and hypothesis testing with product moment correlation with the help of the SPSS version 22.0 program. The results showed that the p value of 0.036 was smaller than the alpha value (α) of 0.05, which means that there is a significant relationship between participation in extracurricular activities and academic achievement of FIK Uncen students class 2017.